GAMIFICATION METHOD IN TEACHING - Pulatova, Maftuna; Saitnazarova , Ullibibi (Educational Research in Universal Sciences, 2023)
This article discusses the application of gamification method in the instruction of foreign languages. The employment of this approach in teaching process by using educational materials such as songs, poems, and art photographs, fosters a positive psychological environment for students and boosts their enthusiasm.